A study on motivation towards customers’ revisit intention to shop at AEON Bandaraya Melaka / Nik Khairunisashira Nik Sin, Nur Ieman Irdina Ali Jafri and Naimah Ismail - Nik Sin, Nik Khairunisashira; Ali Jafri, Nur Ieman Irdina; Ismail, Naimah (2014)
Tourism is one of the largest industries in the world and shopping is an increasingly a favorite activity for tourists. Shopping is known as a major activity that can generates tourism income and also adds to the economic growth. In Malaysia, shopping was the second highest next to accommodation in tourist expenditure of RM18.6 billion said Tourism and Culture Minister, Datuk Seri Mohamed Nazri Abdul Aziz. For that reason, this paper aims to highlight the dimensions of motivation which are the push and pull factors towards customers’ revisit intention in Melaka. The first objective of this study is to identify to what extent the dimensions of motivation which are the push and pull factors encourage customers’ revisit intention to shop at AEON Bandaraya Melaka. The second objective is to determine the most influential factor that affects customers’ revisit intention at AEON Bandaraya Melaka. The results provide strong support for the proposition of this study that two dimensions of motivation which are the push factors and pull factors have significant influential effects on customers’ revisit intention to shop at AEON Bandaraya Melaka. This study also found out that the push factors have the most influential effects on customers’ revisit intention to shop at AEON Bandaraya Melaka.